ASEAN Dalam Neo Kolonialisme dan Imperialisme - Donatus Kladius Marut (Budapest International Research and Critics University, 2015)
Neocolonialism is the geopolitical practice of using capitalism, business globalization, and cultural imperialism to influence a country, in lieu of either direct military control (imperialism) or indirect political control (hegemony). In post-colonial studies, the term neo-colonialism describes the influence of countries from the developed world in the respective internal affairs of the countries of the developing world; that, despite the wars of Spanish American wars of independence at the beginning of the nineteenth century, and decolonisation that occurred in the aftermath of the Second World War (1939–45), the (former) colonial powers continue to apply existing and past international economic arrangements with their former colony countries, and so maintain colonial control.